1986
DOI: 10.1093/oxfordjournals.aje.a114309
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Blood Lead to Blood Pressure in a Longitudinal Study of Working Men

Abstract: The relationship of lead exposure to blood pressure has been examined in a longitudinal study of a cohort of 89 Boston, Massachusetts, policemen. At the baseline examination, subjects had a blood lead determination and three consecutive blood pressure measurements. Triplicate blood pressure measurements were also taken at years 3, 4, and 5. Multivariate analysis revealed that, after correction for previous systolic blood pressure, body mass index, age, and smoking, a high level of blood lead was a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 20 publications
4
32
0
1
Order By: Relevance
“…Staessen et al (13) reported that the addition of gender and age as covariates to models predicting blood pressure reduced the partial correlations of systolic and diastolic blood pressure with B-Pb to a nonsignificant level. Sharp et al (6) observed that a positive relationship between blood pressure and B-Pb was present in black males but not among nonblack males; the inclusion of alcohol use indicators in multiple regression models did not alter the relationship between blood pressure and B-Pb by more than 10%. In black subjects adjusting for tobacco use markedly increase the association between B-Pb and blood pressure.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Staessen et al (13) reported that the addition of gender and age as covariates to models predicting blood pressure reduced the partial correlations of systolic and diastolic blood pressure with B-Pb to a nonsignificant level. Sharp et al (6) observed that a positive relationship between blood pressure and B-Pb was present in black males but not among nonblack males; the inclusion of alcohol use indicators in multiple regression models did not alter the relationship between blood pressure and B-Pb by more than 10%. In black subjects adjusting for tobacco use markedly increase the association between B-Pb and blood pressure.…”
Section: Introductionmentioning
confidence: 93%
“…In black subjects adjusting for tobacco use markedly increase the association between B-Pb and blood pressure. In addition, the relationship was particularly strong in blacks who were infrequent users of caffeine (6).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The longitudinal Boston 84,85 and Glostrup 53 studies applied autoregression to investigate the correlation between lead at baseline and blood pressure during follow-up. The blood lead concentration was expressed on a linear scale in 15 studies and on a logarithmic scale in 16 (Table 1).…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Information for six men was missing for all covariates. The other 89 men were entirely comparable to men without blood lead measurements for all covariates (17).…”
Section: Methodsmentioning
confidence: 80%